Transaminase Enzyme and Liver Histological Profile of Mice Administered Extract of Pegagan (Centella asiatica (L.) Urban) - B Muchtaromah; . Kiptiyah; T T Adi (Media Peternakan, 2011)
The purpose of this study was to determine whether pegagan caused toxic effects on the liver. This study used completely randomized design with four treatments, ie 125, 200, 275 mg/kg BW and control, each treatment consisting of six replicates. Variables observed were the level of GPT, GOT and histological profile of liver. GPT and GOT levels were analyzed by analysis of single variant of 0.05. Histological picture of the liver include central venous dilation, inflammation, and damage to the structure of liver cells were performed by descriptive evaluation. Pegagan leaf extract did not show significant effect on GPT and GOT level in the liver of mice, whereas the histology results did not reveal any visible damage to liver cells in each dose. Administration of pegagan extract up to dose of 275 mg/kg BW was safe and would not cause damage to the liver cells.